No detectable effect of Wolbachia wMel on the prevalence and abundance of the RNA virome of Drosophila melanogaster. Issue 1883 (25th July 2018) - Shi, Mang; White, Vanessa L.; Schlub, Timothy; Eden, John-Sebastian; Hoffmann, Ary A.; Holmes, Edward C.
Abstract : Wolbachia is an endosymbiotic bacterium that can block viral infections in arthropods, generating interest in its potential to control the spread of mosquito-borne disease. Drosophila melanogaster is model organism for Wolbachia infection, and the w Mel strain of Wolbachia can improve host survival following viral infection. However, it is unclear whether w Mel induces anti-viral blocking against the broader native virome of D. melanogaster, or whether the major effect of Wolbachia is a reduction in viral abundance rather than viral clearance. We examined the effect of Wolbachia on viral abundance by comparing the total transcriptome of w Mel-positive and w Mel-negative D. melanogaster populations sampled from six locations in Australia. In addition, we examined the impact of w Mel on individual flies by obtaining transcriptome data from 20 w Mel-positive and 20 w Mel-negative D. melanogaster from the location (Melbourne) with highest density of w Mel. These data revealed high viral abundance in both Wolbachia -positive and -negative populations and individuals. Notably, none of the viral species identified, representing RNA viruses from at least nine families/floating genera, showed evidence of protection by w Mel. Although the viral loads of picorna-like viruses are reduced by w Mel under experimental conditions, we observed no such effect here. These data show that D. melanogaster can harbour abundant RNA viruses regardless of its Wolbachia status and imply that the interaction between Wolbachia and viruses in nature is more complex than simple blocking.